Lao PDR Country Opinion Survey Report (July 2012 - June 2013) - World Bank Group (Washington, DC, 2014)
The Country Opinion Survey for FY2012 in Lao PDR assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Lao PDR perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Lao PDR on 1) their views regarding the general environment in Lao PDR; 2) their overall attitudes toward the WBG in Lao PDR; 3) overall impressions of the WBG s effectiveness and results, knowledge work and activities, and communication and information sharing in Lao PDR; and 4) their perceptions of the WBG s future role in Lao PDR.